2005
DOI: 10.1152/ajpregu.00254.2005
|View full text |Cite
|
Sign up to set email alerts
|

Aging reduces responsiveness to BSO- and heat stress-induced perturbations of glutathione and antioxidant enzymes

Abstract: Aging alters cellular responses to both heat and oxidative stress. Thiol-mediated metabolism of reactive oxygen species (ROS) is believed to be important in aging. To begin to determine the role of thiols in aging and heat stress, we depleted liver glutathione (GSH) by administering l-buthionine sulfoximine (BSO) in young (6 mo) and old (24 mo) Fisher 344 rats before heat stress. Animals were given BSO (4 mmol/kg ip) or saline (1 ml ip) 2 h before heat stress and subsequently heated to a core temperature of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The activation of SOD is usually caused by increased superoxide radical formation (Ji 1993). SOD is a free radical-chain breaking enzyme that catalyzes the dismutation of superoxide radical into oxygen and H 2 O 2 (Halliwell and Chirico 1993), and while it is an important antioxidant defense mechanism in aerobic organisms it can be affected by changes in temperature, as demonstrated by previous studies using animal models (Oztürk and Gümüslü 2004;Morrison et al 2005). In the present study, SOD activity was not affected by heat stress at rest but was reduced when heat stress was superimposed with exercise.…”
Section: Discussionmentioning
confidence: 96%
“…The activation of SOD is usually caused by increased superoxide radical formation (Ji 1993). SOD is a free radical-chain breaking enzyme that catalyzes the dismutation of superoxide radical into oxygen and H 2 O 2 (Halliwell and Chirico 1993), and while it is an important antioxidant defense mechanism in aerobic organisms it can be affected by changes in temperature, as demonstrated by previous studies using animal models (Oztürk and Gümüslü 2004;Morrison et al 2005). In the present study, SOD activity was not affected by heat stress at rest but was reduced when heat stress was superimposed with exercise.…”
Section: Discussionmentioning
confidence: 96%
“…Heat stress was also shown to decrease or inhibit SOD expression and activities [52][53][54]. This inhibition can be attributed to thermal/oxidative inactivation of the enzyme [55].…”
Section: Mitochondrial Antioxidant System and Thermal Sensitivitymentioning
confidence: 97%
“…In this direction Morrison et al (2005) showed that CAT activity significantly decreases with aging, while the activity of GPx remains unchanged during aging. This outcome was not observed in our study and we found that CAT activity does not change and the GPx activity decreases with aging of rats, in both the liver and kidney.…”
Section: Discussionmentioning
confidence: 87%